Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Padang Lawas - Budiharjo, Roy; Mareta, Sigit; Hamzah, Nur Aisyah (Journal of Economics and Management, 2023)
This study was conducted to analyze how the performance of regional financial management of the Padang Lawas district government of North Sumatra Province. The type of research conducted is quantitative descriptive research using secondary data. The data analysis used is to calculate the Regional Financial Independence Ratio, Regional Financial Compatibility Ratio, Regional Financial Growth Ratio and Regional Original Revenue Effectiveness Ratio (PAD). Based on the analysis of the Regional Financial Performance of the Regional Government of Padang Lawas Regency conducted in the 2018-2022 fiscal year period, it is known that the Regional Financial Independence Ratio shows an instructive pattern relationship, the Regional Financial Compatibility Ratio has inequalities in Operating Expenditure and Capital Expenditure, the Regional Financial Growth Ratio in the last 1 (one) year has decreased, and the PAD Effectiveness Ratio shows that the average is at a low level i.e. below 100% or ineffective. Based on these findings, it was concluded that the Financial Performance of the Regional Government of Padang Lawas Regency had not run optimally as expected with the fiscal decentralization function.